Aggression in online gaming: the role of online disinhibition, social dominance orientation, moral disengagement and gender traits among Chinese university students - Wenxuan Gan; Zichao Chen; Zhusheng Wu; Xia Huang; Fang Wang (Frontiers Media S.A., 2024)
IntroductionAggressive behaviors in the online gaming world are frequent and have far-reaching negative effects.MethodTo explore the factors and mechanisms of aggressive in games, we surveyed 945 university students using a framework of social dominance orientation, online disinhibition, moral disengagement, and aggression in gaming, and examined the moderating role of gender traits.ResultsWe found no direct relationship between online disinhibition and aggression in gaming; however, through the mediating role of moral disengagement, online disinhibition indirectly affected aggression in gaming behavior and enhanced social dominance orientation. Social dominance orientation predicted both moral disengagement and aggression in gaming behaviors, and the mediating effect of moral disengagement was confirmed through the indirect influence of moral disengagement on aggression in gaming behavior. Moreover, the moral disengagement mechanism significantly predicted aggression in gaming behavior. Furthermore, femininity and androgyny moderated both social dominance orientation toward moral disengagement and aggression in gaming, while masculinity and androgyny moderated the path from online disinhibition to social dominance orientation. Regarding the path from moral disengagement to aggression, all gender trait moderations were significant.DiscussionThis study reveals the role of the moral disengagement mechanism in the process of game-related aggression, providing theoretical support for the explanation of aggressive behavior, which applies to players of any gender. Moreover, this study confirms the moderating role of gender. Unlike biological sex, gender traits are malleable; androgynous traits offer greater adaptability in various environments. Thus, prevention and intervention efforts against online aggression should include strengthening moral education and properly guiding and fostering androgynous gender traits.